Corneal ulcer due to Achromobacter xylosoxidans. Issue 7 (July 1984) - Newman, P E; Hider, P; Waring, G O; Hill, E O; Wilson, L A; Harbin, T S
Abstract : We report a case of corneal ulcer caused by the opportunistic organism Achromobacter xylosoxidans which developed during chronic topical steroid treatment of an eye with neovascular glaucoma. A. xylosoxidans has probably been underreported as a cause of ocular infection because of confusion between this organism and other Gram-negative organisms, particularly pseudomonas. A. xylosoxidans is resistant to aminoglycosides and some cephalosporins but not carbenicillin. This difference in antibiotic sensitivity patterns between A. xylosoxidans and pseudomonas makes an accurate differentiation between the 2 organisms important. This case was successfully treated after substituting topical carbenicillin for topical gentamicin and amikacin.